Accelerated biological ageing of solar reflective and aesthetically relevant building materials. Issue 2 (3rd July 2019) - Santunione, Giulia; Ferrari, Chiara; Siligardi, Cristina; Muscio, Alberto; Sgarbi, Elisabetta
ABSTRACT: The properties of building materials relevant to their thermal or aesthetical performance can be seriously influenced by the colonization of external surfaces by microorganisms. Deterioration phenomena due to biological aggression cause the loss of energy performance of solar reflective materials because of the decrease of solar reflectance. Bio-deterioration also affects cultural heritage, damaging the aesthetic appearance and thus the historic value. In order to investigate the consequences of biological aggression in short times, an accelerated test method based on a laboratory-reproducible set-up is proposed. Specific and controlled environmental conditions are chosen to accelerate as much as possible biological growth on building materials. In this regard, a reproducible bio-ageing protocol has been outlined and it allows a set of materials to reach an advanced bio-aged level in a short time (8 weeks or less). This test method is aimed to comparatively evaluate different materials under a given set of ageing conditions. Through surface, microstructural and chemical analysis, the evolution of the materials' properties after ageing is investigated. Attention is also paid to bacterial and algal growth rate by analysing time-progressive images.